2015
DOI: 10.1111/poms.12361
|View full text |Cite
|
Sign up to set email alerts
|

How to Compete Against a Behavioral Newsvendor

Abstract: W e investigate newsvendor ordering behavior under competition. We present a laboratory experiment that documents the behavioral ordering regularities in competitive newsvendor environments, and an analytical model extending the standard theory of newsvendor competition by including an optimal best-response policy for competing with a behaviorally biased newsvendor. We test the effectiveness of this policy using an out-of-sample experiment and find that it results in improved market share, service level and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 27 publications
8
68
0
Order By: Relevance
“…To study the ordering behavior in a competitive newsvendor problem, Ovchinnikov et al. () propose a demand‐based behavioral model that incorporates several well‐established newsvendor ordering regularities, including the pull‐to‐center effect, demand chasing, and reference dependence. The OMQ model takes the following forms:qi,t=italicβ0+italicβ1di,t1+italicβ2)(qi,t1di,t1++italicβ3)(di,t1qi,t1+,where qi,t is the observed order quantity by individual i in round t , and di,t1 is the effective demand in round t − 1.…”
Section: Behavioral Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the ordering behavior in a competitive newsvendor problem, Ovchinnikov et al. () propose a demand‐based behavioral model that incorporates several well‐established newsvendor ordering regularities, including the pull‐to‐center effect, demand chasing, and reference dependence. The OMQ model takes the following forms:qi,t=italicβ0+italicβ1di,t1+italicβ2)(qi,t1di,t1++italicβ3)(di,t1qi,t1+,where qi,t is the observed order quantity by individual i in round t , and di,t1 is the effective demand in round t − 1.…”
Section: Behavioral Modelsmentioning
confidence: 99%
“…In addition to Ovchinnikov et al. (), Quiroga et al. () consider a similar situation in which a behavioral newsvendor competes against a management‐science‐driven newsvendor and find that profit losses are orders‐of‐magnitude larger than existing literature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…he chooses high yielding order quantities with larger probability Simon (1955), Su (2008), Kremer et al (2010), Katok (2011), (Ovchinnikov et al 2015) overconfidenc e bias (or, overprecision) tendency of decision maker to overestimate their own opinions due to precise information that they believe they have An overconfident newsvendor will underestimate the variance of demand and make suboptimal ordering decisions. Over-order in low profit-margin Croson et al (2008), Ren and Croson (2013), Ren et al (2017) Cui et al (2013) 4.1 Individual Decision-Making Biases Schweitzer and Cachon (2000) found that the PTC effect observed in their experimental data results were not consistent with alternatives like risk aversion preferences, loss aversion, waste aversion bias, stock out aversion, or underestimating opportunity costs (Table 3), instead they found two explanations for this behavior: (1) individual's preferences to reduce ex-post inventory error; and (2) subjects suffer from anchoring and insufficient adjustment bias.…”
Section: Figurementioning
confidence: 99%
“…So, the model fails to account for heterogeneity in the individuals and thus no single explanation for the observed behavior. Random error model of Su (2008) is also not useful for the newsvendor under competition (Ovchinnikov et al 2015), where a decision-maker can predict some regularities in the ordering pattern of competing newsvendor by applying decision support models.…”
Section: Bounded Rationalitymentioning
confidence: 99%